Validity analysis of the Irritation Scale in a sample of Elementary School teachers: an exploratory study - Merino-Tejedor, Enrique (Anales de Psicología / Annals of Psychology, 2013)
The purpose of the present article is to test the validity of the Spanish version of the Irritation Scale in a sample of 106 Elementary School teachers. Results obtained through the use of the Irritation Scale were compared to those obtained with another instrument, the Brief Burnout Questionnaire adapted for teachers; positive and significant correlations were expected to be found between both instruments. Furthermore, two additional instruments were used, the General Self-Efficacy Scale and the Self-Regulation Scale, with the hypothesis of finding negative correlations between the latter two instruments and the Irritation Scale. Results confirmed the research hypotheses since the Irritation Scale correlated positively and significantly with the Brief Burnout Questionnaire, and negatively and significantly with the other two instruments. Thus, statistical analyses confirm the validation of the Irritation Scale for assessing stress among Elementary School teachers.